2018
DOI: 10.1371/journal.ppat.1007188
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde axonal transport of rabies virus is unaffected by interferon treatment but blocked by emetine locally in axons

Abstract: Neuroinvasive viruses, such as alpha herpesviruses (αHV) and rabies virus (RABV), initially infect peripheral tissues, followed by invasion of the innervating axon termini. Virus particles must undergo long distance retrograde axonal transport to reach the neuron cell bodies in the peripheral or central nervous system (PNS/CNS). How virus particles hijack the axonal transport machinery and how PNS axons respond to and regulate infection are questions of significant interest. To track individual virus particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…Some neurotropic viruses such as alphaherpesvirus can stimulate synthesis of dynein-regulatory factors to promote their transport following neuronal entry [9]. However, we found that reovirus, similar to rabies virus [97], does not require synthesis of new proteins for axonal transport (S3 Fig). During transport in axons, reovirus-containing vesicles remain predominantly non-acidified (Fig 7A and 7B).…”
Section: Plos Pathogensmentioning
confidence: 81%
“…Some neurotropic viruses such as alphaherpesvirus can stimulate synthesis of dynein-regulatory factors to promote their transport following neuronal entry [9]. However, we found that reovirus, similar to rabies virus [97], does not require synthesis of new proteins for axonal transport (S3 Fig). During transport in axons, reovirus-containing vesicles remain predominantly non-acidified (Fig 7A and 7B).…”
Section: Plos Pathogensmentioning
confidence: 81%
“…It is also used to induce vomiting. In addition, it possessed antiviral effects against ZIKV, EBOV, RABV, CMV, HCoV-OC43, HSV-2, EV1, HMPV, RVF, FLUAV, HIV-1 and SARS-CoV-2 (Andersen et al, 2019;Chaves Valadao et al, 2015;Choy et al, 2020;MacGibeny et al, 2018;Mukhopadhyay et al, 2016;Shen et al, 2019;Yang et al, 2018) (https://doi.org/10.1101/2020.03.25.008482). Emetine was proposed to inhibit viral polymerases, though it could have some other targets (Khandelwal et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, its potential cardiotoxicity has restricted its clinical use in the recent years. It was found to process antiviral activity against a broad range of RNA and DNA viruses, including Zika virus, Ebolavirus, Cytomegalovirus, rabies virus, HIV-1, echovirus 1, buffalo poxvirus, bovine herpesvirus 1, peste des petits ruminants virus, Newcastle disease virus, herpes simplex virus-2, metapneumovirus, Rift Valley fever virus, and influenza (Andersen et al, 2019;Chaves Valadao et al, 2015;Khandelwal et al, 2017;MacGibeny et al, 2018;Mukhopadhyay et al, 2016;Yang et al, 2018). Emetine was also identified to inhibit hCoV-OC43, hCoV-NL43, SARS-CoV, MERS-CoV, and MHV-A59 in vitro with EC 50 reported at low micromolar range (Dyall et al, 2014;Shen et al, 2019).…”
mentioning
confidence: 99%